Effect of Omnichannel Implementation on Service Quality, Customer Satisfaction, and Perceived Value in Indonesian Restaurant - Yudhistira Qasthari Putra; Nurdin Sobari (Indonesian Journal of Business and Entrepreneurship, 2024)
Omnichannel in restaurants provides ordering methods through various integrated channels. Customers can place orders using an online platform without waiting for a waiter from a restaurant to help them. Through this method, customers can order food and choose a payment method that affects the customer experience. The research aims to see the effect of omnichannel implementation on consumer behavior in restaurants. The research will examine the relationship between omnichannel implementation and three variables, namely service quality, perceived value, and customer satisfaction. The research method used is quantitative with SEM used to see the relationship between the variables of the study. With this research, it is hoped that knowledge about omnichannel can be better understood academically and practically and that omnichannel can be applied optimally so that it can provide benefits for both business and customers. From the research conducted, it was found that omnichannel influences service quality, perceived value, and customer satisfaction both directly and indirectly. Good omnichannel implementation in restaurants is needed to support the improvement of services that can be offered by restaurants to customers. This research concludes that the application of omnichannel can improve service quality, perceived value, and customer satisfaction in restaurants in Indonesia. Keywords: omnichannel, restaurant, service quality, customer satisfaction, perceived value